2016
DOI: 10.5539/ijbm.v11n10p120
|View full text |Cite
|
Sign up to set email alerts
|

Linking Psychological Empowerment to Job Satisfaction and Organizational Commitment: Investigating the Mediating Effect of Organizational Trust

Abstract: The main purpose of this research is to examine the influence of psychological empowerment and organizational trust on job satisfaction and organizational commitment among Kuwait free trade zone employees. Data were obtained for this research through a set of questionnaire which was divided into four parts and administered to a total of 271 respondents. The results showed that psychological empowerment mainly affects employees' job satisfaction and organizational commitment. The results indicated that two dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
2
0
4
Order By: Relevance
“…Nó đề cập đến thái độ của nhân viên trong những thành tựu và lợi ích họ nhận được. Nếu nhân viên nhận thức về sự công bằng phân phối càng cao thì càng làm tăng sự cam kết duy trì đối với tổ chức 3,11 . Khi nhân viên cảm thấy được đối xử công bằng và bình đẳng với các đồng nghiệp khác, đồng thời sẽ được đánh giá và đánh giá dựa trên năng lực, thành tích làm việc và đóng góp thực sự của họ.…”
Section: Công Bằng Phân Phối (Distributive Justice)unclassified
See 2 more Smart Citations
“…Nó đề cập đến thái độ của nhân viên trong những thành tựu và lợi ích họ nhận được. Nếu nhân viên nhận thức về sự công bằng phân phối càng cao thì càng làm tăng sự cam kết duy trì đối với tổ chức 3,11 . Khi nhân viên cảm thấy được đối xử công bằng và bình đẳng với các đồng nghiệp khác, đồng thời sẽ được đánh giá và đánh giá dựa trên năng lực, thành tích làm việc và đóng góp thực sự của họ.…”
Section: Công Bằng Phân Phối (Distributive Justice)unclassified
“…Loại công bằng này cho thấy rằng, người nhân viên sẽ cảm thấy có sự công bằng trong thủ tục nếu như người quản lý cung cấp thông tin đầy đủ về các quyết định liên quan đến các thủ tục 4 . Công bằng thủ tục ảnh hưởng tích cực đến sự cam kết của nhân viên đối với tổ chức, nhân viên sẽ cam kết với tổ chức nhiều hơn khi công bằng thủ tục được nâng cao 3,11 . Khi các thủ tục được đảm bảo công bằng và minh bạch, nhân viên sẽ cảm thấy được đối xử công bằng và đồng thời cảm thấy tin tưởng và an tâm với chính sách và quy trình của công ty.…”
Section: Công Bằng Thủ Tục (Procedural Justice)unclassified
See 1 more Smart Citation
“…Few studies on the mediating role of organizational trust on the relationship between other organizational variables exist. For example, organizational trust has been found to partially mediate the relationship between organizational justice and organizational commitment (Iqbal & Ahmad, 2016), perceived organizational support and constructive deviance (Kura, Shamsudin, & Chauhan, 2016), specific areas of work-life (workload, fairness, reward, and value), and emotional exhaustion (Bayhan, Metin, & Tayfur, 2016), psychological empowerment, job satisfaction and organizational commitment (Alajmi, 2016), distributive and procedural justice on turnover intention (Aryee, Budhwar, & Chen, 2002) and employee-organizational relationship and innovative work behavior (Yu et al, 2018). A study by Hameed, Arain, & Farooq (2013) on the mediating role of identity-based trust on the relationship between organizational identification and turnover intention indicated that trust partially mediated the negative relationship between the predictor and criterion variable.…”
Section: Organizational Trust As a Mediatormentioning
confidence: 99%
“…Further Wickramasinghe et al, (2018) mentioned that the Job Satisfaction is an essence within an organization that affects the life of people with the organization as whole. As stated by Wickremasinghe et al (2018) numerous empirical researchers(Al-Ababneh et al, 2017;Alajmi, 2016), have recognized that there is a positive relationship between Psychological Empowerment and Job Satisfaction.…”
mentioning
confidence: 99%